Diversifikasi produk melalui pemanfaatan tepung umbi-umbian lokal sebagai pengganti terigu pada UKM bakery di Kota Binjai - Elisa Julianti; Ridwansyah Ridwansyah; Terip Karo-Karo; Halimatuddahliana Halimatuddahliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
The bakery industry is one of the food industries that continues to increase along with the increase in income and changes in people's lifestyles. Increasing the number of bakery industries has an impact on the increasing demand for wheat flour, which in turn can threaten national food security. Faidah Catering Service and Baraqah Q Snack, Cake and Cookies are SME partners engaged in bakery industry in Binjai City. Based on the situation analysis, the problems of both SMEs are low production capacity and competition in the marketing. The use of wheat flour as the raw material makes their products become same as the products produced by other SMEs. The simple processing equipment causes a low production capacity. The proposed problem-solving method for SME partners is product diversification through the use of local tubers in the form of cassava flour and sweet potato flour as raw material. Increased production capacity is carried out by giving and training the use of production equipment in the form of dough mixers and oven grills with large capacity. The results of the activity indicate that the diversification of cake products and cookies using non-flour flour raw materials can be accepted by consumers and increase marketing.